Removal of natural organic matter using hybrid oxidation reactor - Guan, Zhihua (2017)
Untreated wastewater was recycled in Singapore through treatment processes in water reclamation plants and NEWater plant. These treated wastewater are then directed to industry uses and local catchment reservoirs. However, wastewater contains natural organic matter which mainly comprises of humic acid that can lead to lower system performance of the membrane technology used in NEWater plants. Thus, this study aims to investigate the efficiency of using ozone in the removal of humic acid from in aqueous solution. In this study, a hybrid oxidation reactor was first designed and ozone was bubbled into the humic acid solution through an air stone. Humic acid stock solution was prepared and 20 times dilution with deionized water was used as influent for the hybrid oxidation reactor with an initial total organic carbon of about 30 mg/L. Several experiments (ozonation of humic acid solution without buffer, ozonation of humic acid solution with buffer, ozonation of humic acid solution at low pH, ozonation of humic acid solution at high pH ) with duration of 120 mins was conducted and the samples are collected at intervals of 20 mins. Total organic carbon and colour of the samples was recorded and studied. Ozonation of humic acid has achieved a removal rate of at least 80% for colour436 and a removal rate of about 15% to 25% was achieved for total organic carbon. It was found that the concentration of ozone is the limiting agent in this study.